Mathematics Engagement Clinic Grounded on Brain Dominance: Its Effect on Critical and Problem-Solving Skills, and Mathematics Achievement - Rosen Anthony S. Marquez (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Contextualization, localization, and indigenization have touched the ground of the dominant cultural character of learners. The teaching and learning process in the K to 12 curricula has integrated its essence. However, in recent ages,s the border-crossing of digital culture among learners was prevalent in their attitudes and learning preferences. Cognitive preferences such as the students’ brain dominance must be considered in the lesson planning as an additional option. With a transformative worldview through an action research design, the study evoked the effects of Mathematics Engagement Clinic (MEC) grounded on brain dominance or the whole brain theory to critical thinking and problem-solving skills, and mathematics achievement. MEC has different effects on the left and right brain dominant participants in terms of their thinking processes such as critical thinking and problem-solving skills. In particular, left brain dominant participants have a distinct behavioral cognition which the researcher called affirmation behavioral learning. The implication of affirmation behavioral learning to the whole brain theory was a notion that brain dominance groups might have specific behavioral cognition. As for this study, affirmation behavioral learning was evident and observed among left-brain dominant participants. As affirmed by the quantitative results, the enhancement program Mathematics Engagement Clinic (MEC) grounded on the whole brain theory or brain dominance can hone thinking processes such as critical thinking and problem-solving skills, and thereby, improve mathematics achievement. Despite the abnormality distribution of participants in the study MEC has managed to cater to the participants’ preferences. With the positive effect of the enhancement program, MEC grounded on brain dominance on the thinking processes and mathematics achievement of the participants, the researcher has constructed a modular mathematics enhancement program framework as a guide to researchers, and other interested parties in the planning, designing, redesigning and implementing modular mathematics enhancement programs grounded on brain dominance to hone and enhance thinking processes such as critical thinking and problem-solving skills, and thereby, improve mathematics achievement.